2004
DOI: 10.3900/fpj.3.4.194.e
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the degree of flexibility and autonomy in elderly women practicing of tai chi e sedentary

Abstract: This study compares level of fl exibility and functional autonomy in elderly women with .X = 72,61±4,04 years old, participant a tai chi program of Rio de Janeiro State University (UERJ) and a sedentary group of a social project. Was used GDLAM protocol for functional autonomy and goniometry (DANTAS, 1999). The descriptive statistical used (.%). FCL 0,85%; FQ 0,34%; FJ 2,87%; for functional autonomy was: C10M = 26,82%; LCLC = 14,75%;LPS = 21,45%; LPDV = 29,41%. The distribution was considered normal by Kolmogo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…RT+MP also performed better than RT+TC in the 10mW test (Figure 5), possibly due to their higher training volume. The results of the present study corroborate those of other research that evaluated this variable, such as the study by Melo et al (2004), who found improvements in the functional autonomy of seniors who engaged in TC, compared to a sedentary group. Rezende et al (2015) observed that sensorymotor training improved the results of all the GDLAM protocol tests in elderly women when compared to the control group.…”
Section: Discussionsupporting
confidence: 91%
“…RT+MP also performed better than RT+TC in the 10mW test (Figure 5), possibly due to their higher training volume. The results of the present study corroborate those of other research that evaluated this variable, such as the study by Melo et al (2004), who found improvements in the functional autonomy of seniors who engaged in TC, compared to a sedentary group. Rezende et al (2015) observed that sensorymotor training improved the results of all the GDLAM protocol tests in elderly women when compared to the control group.…”
Section: Discussionsupporting
confidence: 91%